Creolizing reflexivity:: Autoethnographic stories and theoretical entanglements - Tistea, Ioana (Reconceptualizing Educational Research Methodology, 2025)
This article contributes to ongoing debates on generating interconnected transformative possibilities for decolonizing knowledge production in Nordic educational research without erasing power differences and tensions. Drawing from my PhD research, I entangle various research practices from the previously ignored or discredited margins, which go beyond hegemonic gazes and approvals for legitimacy. I particularly highlight everyday knowledges stemming from multiple senses, encounters, and unexpected connections, which might seem from a scientific perspective less rigorous or considered research at all. These may disrupt Nordic exceptionalism and color-evasiveness in researchers’ racialised positionalities. I show how the concept of creolization intersects with the method of autoethnography as Anzaldúan autohistoria-teoría with the aim of entangling multiple unequal knowers and knowledges, imagine and experiment with unforeseeable possibilities in and beyond research, and thus creolize reflexivity. This can expand the research imagination with regards to what constitute data generation and analysis, co-researching, co-writing, co-authoring publications, and presenting the research to wider audiences.